New high-Z detectors based on YAlO3:Bi3+ for joint use with tissue equivalent BeO in tandem OSL dosimeter - Yaroslav Zhydachevskyy; Vasyl Stasiv; Oleksandr Poshyvak; Sergii Ubizskii; Zuzanna Pawłowska; Yuliia Rumiantseva; Magdalena Baran; Halyna Zhydachevska; Marek Berkowski; Andrzej Suchocki (Scientific Reports, 2025)
Abstract The work introduces a new type of UV-emitting high-Z OSL detectors based on YAlO3:Bi3+ (YAP: Bi) perovskite. Two kinds of YAP: Bi solid state detectors have been fabricated and compared to BeO Thermalox®995 chips. The first ones are single-crystalline detectors cut from a Czochralski grown crystal. The second are detectors cut from the high-density bulk ceramics prepared by the high-pressure high-temperature (HPHT) pressing technique from nanocrystalline powder derived from sol-gel synthesis. The YAP: Bi ceramic detectors studied suffer from strong thermal fading, which makes their use impractical, at least until technological methods to modify this property of ceramics are found. The single crystalline YAP: Bi detectors show very low thermal fading, a wide linearity range of dose response and a sensitivity comparable to BeO, which together with the optical registration in the same UV range, compatible optical stimulation by blue light and similar registration times in CW-OSL mode make them ideal high-Z detectors that can be used alone or in tandem with BeO detectors.